2013
DOI: 10.1111/j.1744-7941.2012.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Leader–member exchange and industrial relations climate: mediating of participatory management in China

Abstract: This study investigates the link between leader-member exchange (LMX) and the industrial relations climate (IRC) in the Chinese context. More specifically, we propose that the relationship between LMX and the IRC is mediated by effective participatory management. Based on data collected from three manufacturing firms in Zhejiang Province, China, we find that effective participatory management fully mediates the effects of LMX on openness and apathy dimensions of IRC. However, effective participatory management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…In the context of China, LMX has been studied to predict the industrial relations climate (Cheung and Wu ). In our research, we expect that employee perceptions of the formal and informal forms of DM that they experience will affect their attitudes to, and relationship with, their line managers.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…In the context of China, LMX has been studied to predict the industrial relations climate (Cheung and Wu ). In our research, we expect that employee perceptions of the formal and informal forms of DM that they experience will affect their attitudes to, and relationship with, their line managers.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…As well, Bacon, Blyton and Dastmalchian (2005) found associations between positive IR climate and collaborative practices between union and management when introducing organizational changes. More recently, Cheung & Wu (2014) examined labor climate in the context of leadermember exchange and participatory management. This latter study is but one example of the expansion of IR climate research across the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Collins and Smith (2006) found that social climates of trust were related to a firm's capability to exchange and combine knowledge. Cheung and Wu (2014) showed that high-quality leader-member exchange based on trust, coupled with participatory management, leads to greater openness among Chinese workers. Chan (2014) also demonstrated that moral leadership had a direct effect on employee voice in Chinese workers.…”
Section: Trust and Participationmentioning
confidence: 98%